Fractures and survival in multiple myeloma: results from a population-based study - Thorsteinsdottir, Sigrun; Gislason, Gauti; Aspelund, Thor; Sverrisdottir, Ingigerdur; Landgren, Ola; Turesson, Ingemar; Björkholm, Magnus; Kristinsson, Sigurður Y. (Haematologica (Roma), 2020)
Multiple myeloma causes lytic bone lesions and fractures. The impact of fractures on multiple myeloma (MM) survival is unclear. The aim of this study was to evaluate the effect of fractures on survival in MM using data from MM patients diagnosed in Sweden in the years 1990-2013, identified from the Swedish Cancer Registry. Information on date of birth, MM diagnosis, fractures, and death was collected from central registries. A Cox regression model was used to compare survival in patients with and without a fracture at MM diagnosis and another Cox model was used with fracture as a time-dependent variable to assess the effect of fracture on survival after MM diagnosis. Results were adjusted for age, sex, year of diagnosis, and previous fractures. A total of 14,013 patients were diagnosed with MM during the study, of whom 1,213 (8.7%) were diagnosed with a fracture at MM diagnosis, and 3,235 (23.1%) after diagnosis. Patients with a fracture at diagnosis were at a significantly increased risk of death (hazard ratio=1.28; 95% confidence interval: 1.19-1.37). The risk of death was significantly increased in patients with a fracture after MM diagnosis (2.00; 1.90-2.10). The impact of fractures on survival did not change significantly between the two calendar periods 1990-1999 and 2000-2013 (0.98; 0.89-1.08). Our large study shows that MM patients with fractures are at a significantly increased risk of dying compared to those without fractures, which stresses the importance of preventing bone disease in MM.